Long-term outcomes of surgical or endovascular treatment of adult with midaortic syndrome: A single-center retrospective study over a 14-year periodCentral MessagePerspective - Hao Liu, MD, PhD; Tianyue Pan, MD, PhD; Bin Chen, MD, PhD; Junhao Jiang, MD, PhD; Weiguo Fu, MD, PhD; Zhihui Dong, MD, PhD (JTCVS Open, 2024)
Objective: Midaortic syndrome is a rare clinical condition that has been mainly studied in juveniles through case reports and series. This study aims to report the anatomic characteristics and long-term outcomes of 41 adult patients with midaortic syndrome who received open surgical treatment or endovascular treatment over a 14-year period. Methods: A consecutive cohort of 41 adult patients diagnosed with midaortic syndrome at our center between January 2008 and November 2021 were enrolled in the study. Patients’ baseline and anatomic characteristics were collected and analyzed. Primary follow-up outcomes included death and reintervention. Other follow-up outcomes included hypertension and complications. Results: The study enrolled 41 adult patients with midaortic syndrome with a mean age of 37.5 ± 13.4 years. Twenty-five patients received open surgical treatment, and 16 patients received endovascular treatment. Isolated infrarenal lesions were more likely to be found in the endovascular treatment group (P = .005), whereas patients with multiple (P = .002) or intravisceral involvement (P = .001) were more likely to be found in the open surgical treatment group. The open surgical treatment group was more likely to have a lower postoperative peak systolic pressure gradient (P = .020). The 5- and 10-year reintervention-free survivals were 87.7% and 71.7% in the open surgical treatment group and 92.3% and 79.1% in the endovascular treatment group, respectively. Conclusions: Both open surgical treatment and endovascular treatment showed satisfactory long-term efficacy outcomes for adult patients with midaortic syndrome. Given the patients’ relatively young age and long life expectancy, strict and regular lifelong follow-up is necessary.